Influence of curing thermal history on cross-linking degree of a polydimethylsiloxane: Swelling and mechanical analyses - Tiziana Bardelli; Claudia Marano; Francesco Briatico Vangosa (eXPRESS Polymer Letters)
In this work, the change of the elastic properties induced by a change in cross-linking conditions of polydimethylsiloxane is investigated by measuring its shear modulus by dynamic mechanical analysis and correlating it to that predicted from swelling measurements. Polymer cross-linking is performed at different curing temperatures reached with ramps at different heating rates. From both mechanical and swelling measurements, the molecular weight between cross-links, MC, is determined, and its dependency on the applied thermal history is analyzed. The main results are: (i) the elastic modulus of the cured material is not significantly affected by the heating rate adopted, while (ii) the curing temperature has a significant influence on the polydimethylsiloxane mechanical properties. In addition, (iii) MC evaluation from swelling measurements is in good agreement with that estimated from mechanical measurements when appropriate theories are considered. This last result suggests that swelling experiments can be considered as a reliable tool to predict the elastic modulus of the polydimethylsiloxane studied. The quantitative information reported in this paper, also obtainable by the suggested method if other thermal curing histories are applied, is extremely useful for the proper design of devices based on polydimethylsiloxanes.